Arte do tempo no espaço : som e instalações - Silva, Ana Lia Rodrigues da (2015)
The research addresses art installations that converse with the sound, which are the result of the hybridism in Arts, sound, music, visual and spatial, among other transversalities. The field research was carried out at the 31st São Paulo Biennial of Art (2014) and the Contemporary Art Center of Inhotim (Minas Gerais) and explored productions that bring the sound as an experience, used in the deconstruction, documentation or as a sensory experience of objects. The research focus seeks to relate perspectives of the Time in the body of the analyzed art works.